A new family and genus of calanoid copepods (Crustacea) from the abyss of the Atlantic Ocean - Markhaseva, Elena L.; Schulz, Knud (Zootaxa, 2009)
Kyphocalanus gen. nov. is described from female specimens collected at abyssal depths above the sea bed in the Atlantic Ocean. Although the new genus shares the presence of sensory setae on maxilla and maxilliped with other Bradfordian families of the superfamily Clausocalanoidea, it does not fit the diagnosis of any of these families. The family Kyphocalanidae fam. nov. is established for the genus and 4 species are identified, although we only had enough suitable material to name one of them: Kyphocalanus atlanticus sp. nov. Kyphocalanidae is defined by the following apomorphies: maxillule supplied with 3 setae on praecoxal arthrite; maxilla endopod has 8 thick worm-like sensory setae distinctly longer than sclerotized setae of maxilla endites, and the maxilliped shows a 1, 2, 0 setal armament with only worm-like sensory elements of the three praecoxal endites respectively. Segmentation and setation of the swimming legs of the new genus are typical of Clausocalanoidea.